1989
DOI: 10.1002/ijc.2910430609
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer and diet in an asian population—A case‐control study among Singapore Chinese

Abstract: A hospital-based case-control study of diet and colorectal cancer was conducted among Chinese in Singapore (who constitute 77% of the population). A total of 203 cases and 425 controls were included. A history of the usual dietary intake one year prior to interview was taken using a quantitative food frequency questionnaire. Daily intakes of nutrients and selected food items were computed and stratified by tertiles of the control range, to assess risk in low-, medium- and high-intake categories. Effects were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(63 citation statements)
references
References 26 publications
3
59
1
Order By: Relevance
“…9 This may account for the null studies that were conducted earlier in the smoking epidemics during which the extent of cigarette exposure was not sufficient to demonstrate an association with colorectal cancer in the study population. 6,7 Second, the prevalence of cigarette smoking reached its peak in Hong Kong about 20 years earlier than it did in mainland China. 9 This may explain why, unlike the present study, a recent report conducted in mainland China on tobacco-related mortality failed to identify any association with colorectal cancer.…”
Section: Smoking Habitmentioning
confidence: 98%
See 2 more Smart Citations
“…9 This may account for the null studies that were conducted earlier in the smoking epidemics during which the extent of cigarette exposure was not sufficient to demonstrate an association with colorectal cancer in the study population. 6,7 Second, the prevalence of cigarette smoking reached its peak in Hong Kong about 20 years earlier than it did in mainland China. 9 This may explain why, unlike the present study, a recent report conducted in mainland China on tobacco-related mortality failed to identify any association with colorectal cancer.…”
Section: Smoking Habitmentioning
confidence: 98%
“…5 The relationship between cigarette smoking and colorectal cancer in Chinese had previously been reported in 3 case-control studies and 1 cohort study. Two of the case-control studies, one on Singapore Chinese and another on northern Chinese, 6,7 were conducted more than a decade ago, whereas the other 2 studies, a cohort study from Shanghai and a case-control study on adult deaths in Hong Kong,8,9 were reported in 1997 and 2001, respectively. In all 4 studies, no association could be found between cigarette smoking and colorectal cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Michels et al (36) reported separate RR from two large US cohorts in their study, the Nurses' Health Study (NHS) (36a) and the Health Professionals Follow-up Study (HPFS) (36b) ; we counted the report as two prospective studies. Finally, our meta-analysis included twenty-five case-control (11,15,20,26,(28)(29)(30)(31)(33)(34)(35)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) and sixteen cohort studies (17,19,21-25,27,32,36a,36b,37,52-55) .…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…6 Sixteen out of 20 case-control studies supported an inverse association between high coffee consumption and colorectal cancer risk. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, the results of those studies may have been affected by selection bias or recall bias due to retrospective assessment of coffee consumption and other lifestyles-related factors after diagnosis of cancer. In contrast, results from prospective cohort studies have been inconclusive.…”
mentioning
confidence: 99%